Determinants of Profitability in Pharmaceutical and Health Sector Companies in Indonesia Stock Exchange - Santini, Ni Made; Sari, Ni Made Taman; Suarka, Ida Bagus Komang (International Journal of Scientific Research and Management (IJSRM), 2022)
The company's management plays an important role in maintaining the sustainability of the company's operations and also in the company's overall assessment. Having reliable management is important, but a company leader also requires an analysis of financial ratios. The capital market is now increasingly in demand by the public. Not only as a source of funding for companies, is the capital market now a means for investors to invest. The average profitability as an instrument for investors to invest in fluctuating pharmaceutical companies tends to decline. This allows investors to experience risk. For that investors need to know what the factors that can affect profitability are. This study aims to analyze the effect of financial ratios on the profitability of pharmaceutical companies listed on the Indonesia Stock Exchange. The financial ratios used are the company's profitability ratios, returns on assets, Debt to Equity Ratio. Data collected by documentation study through www.idx.co.idthen analyzed by multiple linear regression with the help of software SPSS V.21, The results show that there is a positive and insignificant relationship between total asset turnover and Return on Assets, there is a positive and significant relationship between the current ratio and the Return on Assets in pharmaceutical and health companies, and there is a negative and insignificant relationship between the debt to equity ratio. Based on the results of the study, suggestions that can be given to the pharmaceutical sub-sector companies are to increase the use of the company's current assets such as maintaining cash flow, managing inventory and controlling accounts receivable. And can increase the use of corporate debt to increase the company's assets which are expected to increase company profits.